New evidence on the frequency and severity of medical malpractice claims - Danzon, Patricia Munch, 1946-; Rand Corporation; Institute for Civil Justice (U.S.) (Santa Monica, CA : RAND, 1986)
This report updates an earlier analysis (RAND/R-2870-ICJ/HCFA) of the effects of demographic, medical, and legal factors on the frequency and severity of medical malpractice claims. Using claims data from 1975-1984, the author analyzes the effects of tort reform on malpractice claims after taking into account the effects of other variables that have previously been shown to correlate with claims frequency and severity. The evidence from the study suggests that the last round of tort reforms affected the frequency and severity of malpractice claims over the decade 1975-1984 in a way broadly consistent with theory and previous evidence. Claim frequency per physician has grown at roughly 10 percent a year and severity has increased at twice the consumer price inflation rate. Nevertheless, tort changes have had some effect. States that enacted shorter statutes of limitations and set outer limits on discovery rules have had less growth in claim frequency than would otherwise have been predicted. States with statutes permitting or mandating the offset of collateral benefits had 14 percent fewer claims, and 11 to 18 percent smaller payouts, than would otherwise have been predicted. States with caps on awards have reduced severity by 23 percent. Arbitration statutes appear to have increased claim frequency but reduced average severity.
"Institute for Civil Justice."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Insurance, Physicians' liability -- United States; Malpractice -- United States; Medical personnel -- Malpractice -- United States